Formulation of high performance grease from waste oils and red gypsum - Wan Nur Athirah, Wan Mohammad Hamdan (2014)
This thesis describes a formulation of high performance grease from waste oils and red gypsum. The objectives for this study are to develop high performance grease from different types of waste oils and red gypsum and also to determine the best quality of grease based on different ratio of red gypsum and fumed silica. Grease is a semi-solid lubricant that the composition comprising of three major components, a lubricating base oil, a thickener and an additive. The grease formulated using four different waste oils as base oil which is recovered oil from waste emulsions, waste cooking oil, used oil and silicone oil, while fumed silica and red gypsum are used as thickener, molybdenum disulphide as additive and iron octoate as anti-oxidant agent. Different ratios of fumed silica and red gypsum were tested in this research to determine which ratio will formulate the best grade of grease based on National Lubricating Grease Institute (NLGI) number grade grease. The proportions of fumed silica and red gypsum involves are (100% red gypsum), (80% red gypsum, 20% fumed silica), (60% red gypsum, 40% fumed silica) and (50% red gypsum and 50% fumed silica). Evaluation is carried out using American Society for Testing and Materials (ASTM) to characterise the new formulation of grease in term of penetration test, dropping point test, type of thickener and amount of oil separated. This test is important to find the best formulation of grease from waste oils and red gypsum, by comparing it with greases that available in markets. It was discovered that the formulated grease has no dropping point even after 240°C of heating which proves that the grease has a stable structure at higher temperature. When the amount of fumed silica and red gypsum increases, oil separation decreases while the consistency of the grease increases. Grease properties are not only dependent on the composition of the base oil but also on the size and configuration of particles of the thickening agent. The more fumed silica contains in the grease, better the grease‟s quality. Greases with a higher grade number are firmer, tend to stay in place and are a good choice when leakage is concern. From the result of the experiment, grease was well made using base oil from silicone oil, following by waste emulsion. Smooth grease was made by using waste cooking oil, while grease cannot form when using used oil.